The effect of movement rhythm on performance in synchronized swimming and gymnastics - Chairopoulou, L. (Serbian Journal of Sports Sciences, 2009)
Performance efficiency for repetitive arm movements in synchronized swimming and gymnastics on apparatus was measured to find if there was a relationship between the two similar sports in terms of personal rhythm. Ten gymnasts and ten synchronized swimmers aged 10.6 and 10.9 years were tested in three different rhythms (slow, personal and fast) while holding a lever arm. The movement was flexion-extension in the vertical plane. The mean personal rhythms were not statistically different between the two groups of athletes (2-tailed t test). The work produced was measured to test the effect of rhythm on efficiency. The overall Multivariate test (2-way repeated measures ANOVA) was found to be statistically significant. The greatest efficiency was achieved during the slow rhythm, with ~68% of the max work produced. It is suggested that slow rhythms are more efficient for performance and learning in young athletes. With such athletes, rhythm plays a very important role in the performance of a simple motor task of flexion-extension of the arm. Work produced is directly related to the movement rhythm, and performance is increased when movement rhythm is slow and suited to the general motor framework of the child.